EVALUASI KONDISI TERMAL BANGUNAN GREENHOUSE DENGAN MATERIAL ATAP POLYCARBONAT UNIVERSITAS MUSASMUS MERAUKE - Muchlis Alahudin; Anton Topan; wahida wahida; Dwilis Sarkol; Didik Didik (AGRICOLA, 2013)
The aimof the research was to evaluate the thermal comfort of greenhouse which has roof polycarbonate.The research used quantitative approach. The variables for comfort standards were temperature, humidity and air movement. The determination of the case was based on the criteria of greenhouse roof material and Environment conditions surrounding thegreenhouse. Data were obtained by using instruments of, i.e. Thermo-Hygrometer and Anemometer. Data were analyzed quantitatively using convenience standard of research.The results showed that there were significant differences between temperature in greenhouse and temperature out greenhouse. Oriented building effect, used element building and environment condition affected to temperature inside and outside greenhouse because design greenhouse was not in standard concept for the greenhouse building for tropic condition